Kedudukan Hadist Sebagai Dasar Pendidikan Islam - Ramadhanul Ikhsan; Cisia Padila; Erman; Radhiatul Hasnah (PT. Banjarese Pacific Indonesia, 2024)
The importance of Islamic education in the lives of all individuals cannot be ignored. Education is considered an important means to achieve life goals, both in happiness in this world and the hereafter. One of the basics of Islamic education that is used as a reference is the hadith. In this article, researchers present the important role of hadith in the context of Islamic education. The research uses the literature study research method, which involves a series of activities that focus on collecting data from literature studies. The research uses books about hadith as the main data source, this process includes reading, recording and managing the necessary data. In data analysis, researchers apply a qualitative approach, namely efforts to organize and sort data. The goal is to create manageable units of data, implement systematic methods, look for patterns, and ultimately identify important things worth studying. The final stage involves the decision to share the research results with others, conveying the findings that have been discovered during the research process. The research results show that the position of hadith in Islamic education has similarities with the Koran as the main reference, but the two also have differences. Even though the Qur'an is considered a global revelation that requires interpretation, hadith have an important role in providing explanations of the concepts contained in the Qur'an, including in the educational context. Hadith also serve as examples and guidelines for individuals in living their lives according to Islamic teachings.